2017
DOI: 10.1021/acscentsci.7b00160
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of CO2 Catalyzed by a Heterogenized Zn–Porphyrin Complex with a Redox-Innocent Metal Center

Abstract: Transition-metal-based molecular complexes are a class of catalyst materials for electrochemical CO2 reduction to CO that can be rationally designed to deliver high catalytic performance. One common mechanistic feature of these electrocatalysts developed thus far is an electrogenerated reduced metal center associated with catalytic CO2 reduction. Here we report a heterogenized zinc–porphyrin complex (zinc(II) 5,10,15,20-tetramesitylporphyrin) as an electrocatalyst that delivers a turnover frequency as high as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
132
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 43 publications
4
132
0
Order By: Relevance
“…While abundant research has focused on the catalyst and support development, a thorough analysis between the two different CO 2 electrolyzer configurations (flow‐by and flow‐through) is still lacking . Is the increased CO 2 supply in flow‐through worth the higher ohmic resistance caused by CO 2 bubbles in the electrolyte?…”
Section: Introductionmentioning
confidence: 99%
“…While abundant research has focused on the catalyst and support development, a thorough analysis between the two different CO 2 electrolyzer configurations (flow‐by and flow‐through) is still lacking . Is the increased CO 2 supply in flow‐through worth the higher ohmic resistance caused by CO 2 bubbles in the electrolyte?…”
Section: Introductionmentioning
confidence: 99%
“…The M–N–C material is usually obtained by pyrolyzing a precursor containing M, N, and C. However, the preparation process of this method is not easy to control and the coordination between M and N cannot be guaranteed. Metalloporphyrins have been widely studied because of their special coordination structures . Although porphyrins have been shown to have electrocatalytic effects, they are less stable and decompose at higher processing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Metalloporphyrins have been widely studied because of their special coordination structures. [19][20][21] Although porphyrinsh ave been shown to have electrocatalytic effects, they are less stable and decompose at higherp rocessing temperatures. In addition, metalloporphyrins and derivatives are often used as molecular catalysts and are used to catalyze CO 2 RR or even HER.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Among these kinds of metal-organic based catalysts,t he metal centers usually act as catalytic active sites.However,it is of note that the main electrocatalytic active sites in Znbased complexes or metal-organic frameworks (MOFs) are usually not the metal center for CO 2 RR process,owing to the fully occupied 3d orbital of Zn II ,but the ligands coordinating with the Zn centers. [9] This bestows new opportunities to optimize the electrocatalytic activity by tuning the ligand itself.F rom another aspect, it has been shown that an electron-rich active center could facilitate CO 2 molecule activation by enhancing electron movement from the active sites to the antibonding orbitals of CO 2 and coupling with protons generating *COOH (the key intermediate for CO production). [7c, 10] Thus,i ncreasing the charge density on the catalytic sites would be ap romising strategy to enhance CO 2 RR activity.T ot his end, we propose an ew strategy to induce more electron density on the ligand sites of ZIFs by apost-treatment process.Byv irtue of ligand doping process, an ew ligand with strong electron-donating ability could act on the MOFs to induce more charge density on the adjacent original ligand sites,s ubsequently enhancing their electrocatalytic activity towards CO 2 RR.…”
mentioning
confidence: 99%